Threonine Need of Growing Female Broilers - Corzo, A.; Kidd, M.T.; Kerr, B.J. (International Journal of Poultry Science, 2003)
A study was conducted to evaluate Thr responses in female broilers from 30 to 42 days of age. Commercial Ross x Ross 508 females were randomly placed into battery cages. A test diet was formulated to provide 0.55% total Thr; progressive increments of 0.05% Thr at the expense of a filler created the experimental diets, up to 0.80% Thr. A conventional-type control diet (0.70% total Thr) was formulated to validate the titration diet which was composed in part by peanut meal, which was necessary to generate a Thr deficiency. Performance of birds fed the control diet was similar (P < 0.05) to the titration diet containing equal Thr (0.70%). Deficiency effects of Thr were seen for most variables. Furthermore, linear or quadratic responses occurred for most parameters measured. Optimization of dietary Thr was feasibly calculated for body weight gain and feed conversion, reaching dietary optimums (95% of the asymptote) at 0.69 and 0.71%, respectively. Carcass as well as breast meat improved in a linear manner with increasing dietary Thr. A hypothetical sigmoidal response exhibited by plasma Thr is in close agreement with the Thr requirements extrapolated from live performance measurements. Threonine response estimates obtained in present experimentation are equal to or higher than those previously reported, perhaps as a consequence of the environment to which the birds were exposed to, possibly translating into modifications of associated maintenance and growth requirements for Thr. However, values obtained for the 30 to 42 day-time period are in close agreement with current NRC (1994) recommendations from 21 to 42 days of age.